The effect of nitride and titanium carbonitride coatings on wearing of cold forming tools - Suski,Cássio Aurélio (2008)
This research studies the effects of plasma-nitriding and titanium carbonitriding mixtures on the wearing resistance of mechanical forming dies for special fixing elements manufacturing. The main focus is the abrasion wear rate, characterized by the friction between the surfaces of the raw material and die. Three different configurations were used for the VF 800AT steel dies, chosen among the ones that had shown high waste rates before coating. Industry and laboratory trials were performed to compare the wear behavior. The coated dies had better results in contrast with others. The plasma-nitriding dies (with a small white layer) showed lower wear resistance (higher wear rate) when compared with titanium carbonitriding dies. That was caused by the excellent hardness of the titanium carbonitriding and the good adherence.